REGIONAL INFLATION CONTROL TEAM MANAGEMENT (TPID) AS AN EFFORTS TO CONTROL INFLATION IN BLITAR DISTRICT - Mohammad Taufan Nahdhi (Universitas Islam Kadiri, 2020)
The low and stable inflation is a recondition to reach a society welfare. In the other hand, the source of inflation in Indonesia not only comes from the government that can be controlled by Bank Indonesia, but also from the demand side. So, the inflation manager needs a cooperation and coordination across instances, that is Bank Indonesia and government. The government and Bank Indonesia transformed an inflation monitor and control team at the central level on 2005, the strengthening coordination is continued by establishing the regional inflation control team (TPID) on 2008. In order to control and reduce the inflation, it is needed to have a strategic plans through a cooperation of regional institution by establishing the regional inflation control team (TPID) of Blitar District in which it will work to maintain the inflation in Blitar District. So, this research aims to know how is the work management that is implemented by TPID Blitar District on controlling the inflation. According to research hypothesis, how is the work management of TPID Blitar District on controlling the work management in Blitar District?. This research is filed research which uses a quantitative descriptive approach. The research subjects of this research are the secretary and TPID member of Blitar District. The data from this research is collected by observation, interview, and documentation technique which is validated by using triangulation source, then it is analysed through reduction, display, and conclusions stages. The research shows that work management of TPID Blitar District on controlling inflation is based on the inflation control guidance which set through governor regulations number 10 year 2015. TPID Blitar District has been implemented management functions indirectly, because the inflation control process that is done by TPID Blitar District has been in line with planning, organising, implementing and controlling function. The management of inflation control which is done by TPID Blitar District has been successfully enough in which the inflation in Blitar District is relatively controlled and stable. Thus, the researcher conclude that the management of inflation control that is done by TPID Blitar District is effective enough with the contribution that they managed to achieve as like as TPID goals.